2006
DOI: 10.1128/mcb.00353-06
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Receptor Activator of NF-κB Ligand Gene Expression by 1,25-Dihydroxyvitamin D3 Is Mediated through Multiple Long-Range Enhancers

Abstract: RANKL is a tumor necrosis factor (TNF)-like factor secreted by mesenchymal cells, osteoblast derivatives, and T cells that is essential for osteoclastogenesis. In osteoblasts, RANKL expression is regulated by two majorSkeletal remodeling in adults occurs through the coupled actions of bone-forming osteoblasts and bone-resorbing osteoclasts (17). The latter are terminally differentiated, multinucleated cells of the monocyte-macrophage lineage (63). The process of osteoclastogenesis is highly complex and is orch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
214
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(224 citation statements)
references
References 81 publications
6
214
3
1
Order By: Relevance
“…Transcription factors, such as vitamin D receptor (VDR), Runx2, cAMP response element binding protein (CREB), and STAT3, are known to associate with this RANKL gene regulatory region (24,27). We found that Shn3 does not activate transcription from this reporter when the CREB binding sites are deleted (Fig.…”
Section: Reduced Expression Of Rankl By Osteoblastic/stromal Cells Lamentioning
confidence: 76%
See 1 more Smart Citation
“…Transcription factors, such as vitamin D receptor (VDR), Runx2, cAMP response element binding protein (CREB), and STAT3, are known to associate with this RANKL gene regulatory region (24,27). We found that Shn3 does not activate transcription from this reporter when the CREB binding sites are deleted (Fig.…”
Section: Reduced Expression Of Rankl By Osteoblastic/stromal Cells Lamentioning
confidence: 76%
“…TNFSF11 gene expression is controlled by a variety of distal and proximal regulatory regions (21,24,25). We focused on a conserved regulatory region located 76 kb upstream of the transcriptional start site that had been described by two independent groups as important for calciotropic agent responsiveness in vitro and in vivo (26).…”
Section: Reduced Expression Of Rankl By Osteoblastic/stromal Cells Lamentioning
confidence: 99%
“…Currently, there is only one other report of a distal transcriptional enhancer: the RankL distal regulatory enhancer (DCR) that affects bone mass. When deleted, DCR caused HBM due to reduced osteoclast activity, leading to a lower rate of bone remodeling similar to that observed in humans and mice with hypoparathyroidism (25,26).…”
Section: Discussionmentioning
confidence: 97%
“…42 Mouse RANKL expression has been shown to be upregulated by 1,25-dihydroxyvitamin D3 and PTH through long-range distal enhancer regions. 43,44 Further, Runx2/Cbfa1 has been shown to potentiate PTH stimulation of RANKL through a site in the distal control region. 45 Recent evidence also suggests that RANKL expression in T cells is regulated by c-Fos through a distal enhancer region.…”
Section: Discussionmentioning
confidence: 99%